Pertumbuhan Bagi Hasil dan Jual Beli Pada Peningkatan Laba Bersih Bank Umum Syariah - Anita Nurahmi (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
This research method used is the method of approach of explanation (explanatory research), that is, to best the hypothesized relationship between the variables. The variables studied are variable X is the growth of profit sharing, buying and selling, while variable Y is net profit growth. The population of the research is as much as 12 Islamic Banks. Sample selection technique uses judgment sampling and obtained a sample of three (3) Islamic commercial bank data collection technique used is the study of the document that examines the financial statements of the years 2011-2015 were obtained from the official website Indonesian Bank (BI). Data analysis and processing techniques used are accounting analysis and multiple linear regression analysis, the classic assumption test (test for normality, multicollinearity test, heteroscedasticity test and autocorrelation test, test hipotesys correlation coefficient analysis coefisien determination).